A Method for Determining the Mechanical Parameters of Solution Pore and Crevice Limestone Based on Porosity - Zheng Hu; Tao Wen; Kexun Zheng; Yankun Wang (Advances in Civil Engineering)
Limestone stratum has great anisotropy, which is distributed from large karst caves, pipelines, and faults to small solution pores, and crevices. In this paper, uniaxial compression tests of solution pore and crevice limestones from Mamaya I hydropower station and Ronglai hydropower station are conducted, and the porosity of these limestones is measured. The results show that there is a good power function relationship between compressive strength and the porosity of the solution pore and crevice limestone. Based on the Hoek–Brown criterion, the method for determining mechanical parameters of the solution pore and crevice limestones is proposed, taking the porosity of the rock into consideration. Then, the relationships between the rock mass parameters mb, s, and a and the porosity n are deduced. Based on the proposed method, the variation laws of the mechanical parameters of the limestones, including uniaxial compressive strength (UCS), tensile strength, deformation modulus, shear strength parameters are analyzed. The proposed method simplifies the complexity of mechanical parameters selection by quantifying GSI, avoids the subjectivity and uncertainty, and has good reliability and suitability in the pore and crevice limestone stratum, which has a certain guiding significance for the construction of similar sites.